1978
DOI: 10.1021/bi00606a001
|View full text |Cite
|
Sign up to set email alerts
|

Production and properties of the α core derived from the cyclic adenosine monophosphate receptor protein of Escherichia coli

Abstract: Proteolytic digestion of the cyclic adenosine monophosphate (cAMP) receptor protein (CRP) in the presence of cAMP results in the formation of a resistant core molecule. The CRP core retains the dimeric structure and cAMPbinding properties of the native CRP, while cAMP-dependent DNA binding is lost. CRP consists of two identical polypeptides of molecular weight 22 500. The CRP cores formed after proteolytic digestion in the presence of 0.1 mM cAMP differ in molecular weight: subtilisin and trypsin CRP cores, ~1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
90
2

Year Published

1980
1980
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 17 publications
1
90
2
Order By: Relevance
“…The protein has M, 45 000 and it is composed of 2 apparently identical subunits [ll]. In the presence of CAMP limited proteolytic digestion of CRP with subtilisin results in a resistant N-terminal core, a-CRP, which retains the dimeric structure and CAMP binding activity but has lost CAMP-dependent DNA-binding capacity at pH 8 as judged by the nitrocellulose filter assay [12,13]. However, from a thermal denaturation study on (u-CRP was prepared essentially as in [ 131 in the following way.…”
Section: Introductionmentioning
confidence: 99%
“…The protein has M, 45 000 and it is composed of 2 apparently identical subunits [ll]. In the presence of CAMP limited proteolytic digestion of CRP with subtilisin results in a resistant N-terminal core, a-CRP, which retains the dimeric structure and CAMP binding activity but has lost CAMP-dependent DNA-binding capacity at pH 8 as judged by the nitrocellulose filter assay [12,13]. However, from a thermal denaturation study on (u-CRP was prepared essentially as in [ 131 in the following way.…”
Section: Introductionmentioning
confidence: 99%
“…This model was suggested on the basis of computer modelling on the interactions between DNA and the polypeptide acarbon backbone of CBP, based on the 2.9 A resolution crystal structure of the CAMP -CBP complex [8]. If this hypothesis is correct, the N-terminal core of CBP, aCBP, produced by subtilisin digestion of the CAMP -CBP complex, in which the small carboxy-terminal domain has been removed [9], should not bind to DNA. Electron microscopy has shown that the binding of CBP non-specifically to DNA results in the formation of a complex with regular striations along the DNA whose length is -&times shorter than that of free DNA [lo].…”
Section: Introductionmentioning
confidence: 99%
“…The sequence also contains several stretches that resemble the CRP-binding site in the gal operon (10). Also available are the proteins involved in the regulation of the ara operon: araC protein (11), CRP (12), and RNA polymerase (13).…”
mentioning
confidence: 99%
“…CRP was purified as described (12), and araC protein was purified as described (11), with the substitution of a hydroxyapatite column for the DEAE-Sephadex column. It was loaded in 0.014 M potassium phosphate buffer at pH 6.9, 10% (vol/vol) glycerol, 0.01 M L-arabinose, 1 mM EDTA, and 1 mM dithiothreitol and eluted in the same buffer with the phosphate raised to 0.13 M.…”
mentioning
confidence: 99%